Managing data subject access requests - Griffith, Richard (British journal of community nursing, 2017)
The Data Protection Act 1998 requires district nurses to process personal patient data fairly and lawfully by keeping accurate, contemporaneous and secure records. Patients who have concerns about the accuracy of their record can seek access to the record under the 1998 Act. In this article, Richard Griffith considers the requirements for requesting and granting access to a patient to view and obtain a copy of their health record.